menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Which equation is equivalent to 4(2 - 5x) = 6 - 3(1 – 3 x) ? (A) 8x = 5 (B) 8x=17 (C) 29x = 5 (D) 29x =1
asked
Nov 22, 2021
10.4k
views
1
vote
Which equation is equivalent to
4(2 - 5x) = 6 - 3(1 – 3 x) ?
(A) 8x = 5
(B) 8x=17
(C) 29x = 5
(D) 29x =1
Mathematics
high-school
Ballu Rocks
asked
by
Ballu Rocks
6.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
5
votes
Answer:
c is the correct answer
29x=5
Jagan
answered
Nov 25, 2021
by
Jagan
6.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
3
votes
answer:
C) 29x=5
reason:
first, distribute the parentheses
this will make your equation 8-20x=6-3+9x
simplify to get 8-20x=3+9x
add 20x to both sides to get 8=3+29x
subtract 3 from both sides to get 5=29x
Sasigarn
answered
Nov 27, 2021
by
Sasigarn
5.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
6.5m
questions
8.6m
answers
Other Questions
What is the least common denominator of the four fractions 20 7/10 20 3/4 18 9/10 20 18/25
What is 0.12 expressed as a fraction in simplest form
Solve using square root or factoring method plz help!!!!.....must click on pic to see the whole problem
What is the initial value and what does it represent? $4, the cost per item $4, the cost of the catalog $6, the cost per item $6, the cost of the catalog?
What is distributive property ?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org